Comparative histopathology of three Serotypes of live infectious bronchitis vaccine (IB88 – 4/91 – H120) in broiler chickens - Barari, Mohammad; Khorrami, Shima; Mortazavi, Seyyed Pejman; Bahonar, Alireza; Charkhkar, Saeed (Journal of Poultry Sciences and Avian Diseases, 2024)
Infectious bronchitis in birds, caused by a coronavirus, is a highly contagious viral disease that causes economic losses in the poultry industry worldwide. It affects the respiratory, urinary, and genital tracts, and control and prevention are focused on vaccination and biosecurity measures. This study compares histopathological lesions caused by IB88, H120, and IB4-91 vaccines in broiler chickens aged 1 to 5 days. One hundred Ross 308 chickens were divided into four groups: group 1 received the IB4-91 vaccine, group 2 was administered the H120 vaccine, group 3 received the IB88 vaccine, and group 4 served as the control group. Over a period of five days, starting from the second day, five chickens from each group were randomly selected and euthanized. Histopathological samples were collected from the trachea, lungs, and kidneys, processed into slides, and examined under an optical microscope for comparative analysis. When comparing the control and vaccinated groups, there were significant differences regarding histopathological indicators. These included hyperemia and infiltration of inflammatory cells in the kidney, lung hyperemia, infiltration of inflammatory cells, necrosis of respiratory epithelium, and hyperplasia of tracheal mucous cells. Differences were noted between the IB4-91 and H120 groups regarding inflammatory cell infiltration, respiratory epithelium necrosis, tracheal mucous cell hyperplasia, and renal hyperemia. Similarly, variations were observed between the IB88 and H120 groups regarding respiratory epithelium necrosis and tracheal inflammatory cell infiltration. Furthermore, differences were identified in tracheal mucosal hyperplasia and renal hyperemia between the IB4-91 and IB88 groups. These findings highlight distinct histopathological responses induced by different vaccines in broiler chickens and emphasize the importance of vaccine selection in poultry health management.